The Construction of Fe-Compounds Doped Porous Carbon Nanofiber and Carbon Nanotube Composite Material by One-Step Carbonization and CVD for Li-Ion Capacitor. Issue 6 (1st January 2019) - Ju, Jingge; Lv, Yi; Wang, Liyuan; Liu, Weicui; Li, Zongjie; Kang, Weimin; Cheng, Bowen
Abstract : In this paper, the Fe-Compounds (FeF2 and Fe2 O3 ) doping porous carbon nanofiber & carbon nanotube (FeCD-PCNF&CNT) composite material is firstly prepared by electro-blown spinning followed by pretreatment and one-step carbonization & chemical vapor deposition (CVD) processes. The CNTs are uniformly growing on the PCNF skeleton which deeply increased specific surface area (from 334.066 to 743.402 m 2 g −1 ) and enhanced electrical conductivity (from 42.22 to 149.48 S cm −1 ) comparing to those of PCNF, and large number of hierarchical-pores are existed. In addition, the Fe-Compounds are uniformly distributed on the PCNF skeleton which provided numerous active sites. The obtained FeCD-PCNF&CNT as an anode material for Li-ion capacitors exhibited high energy density and power density (76.1 Wh kg −1 at 0.075 kW kg −1, 15.4 Wh kg −1 at 7.5 kW kg −1 ), which had broad application prospect in the energy storage field. Moreover, the composite materials with special structure and excellent properties may realize the other applications in the fields of adsorption, water treatment, etc., and the prepared method has a great industrialization potentiality.